Flashbacks in film : a cognitive and multimodal analysis - Gordejuela, Adriana, 1989- (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines film flashback as a rich multimodal narrative device, analyzing the cognitive underpinnings of film flashbacks and the mechanisms that lead viewers to successfully comprehend them. Combining a cognitive film theory approach with the theoretical framework proposed by Blending Theory, which claims that human beings' general ability for conceptual integration underlies most of our daily activities, this book argues that flashbacks make sense to the viewer as they are specifically designed for the viewer's cognitive understanding. Through a mixture of analysis and dozens of case studies, this book demonstrates that successful film flashbacks appeal to the spectator's natural perceptual and cognitive abilities, which spectators exercise daily. This book will serve as a valuable resource for scholars interested in film studies, media studies, and cognitive linguistics"--
Introduction: A cognitive approach to film -- Flashbacks in film -- Blended joint attention -- Viewpoint compression -- Time compression -- The whole picture.
OCLC-licensed vendor bibliographic record.
Keywords: Flashbacks; Memory in motion pictures; Motion pictures and language; Motion pictures -- Psychological aspects; Motion picture audiences -- Psychology; SOCIAL SCIENCE / Media Studies; PERFORMING ARTS / Film & Video / General; PERFORMING ARTS / Film & Video / History & Criticism